Resposta
![2(x - 3) \geqslant 3 + 7 2(x - 3) \geqslant 3 + 7](https://tex.z-dn.net/?f=2%28x+-+3%29+%5Cgeqslant+3+%2B+7)
![\geqslant \geqslant](https://tex.z-dn.net/?f=+%5Cgeqslant+)
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
2(x- 3)⩾3+7
2x - 6 ≥ 3 + 7
2x ≥ 3 + 7 +6
2x ≥ 16
x ≥ 16/2
x ≥ 8
Perguntas interessantes
Matemática,
10 meses atrás
Biologia,
10 meses atrás
Biologia,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Ed. Técnica,
1 ano atrás